Egy novella komplex megközelítése: szoros olvasás és kontextusteremtő értelmezés: (William H. Gass: Rovarok rendje) - Molnár, Gábor Tamás (Studia Litteraria, 2019)
This article offers an interpretation of the short story “Order of Insects” by the American writer William H. Gass. The interpretation is intended as a methodological demonstration of short story analysis, as it shows a way to develop a close textual analysis from a few guiding questions. The opening question is simultaneously generic and thematic, as readers are encouraged to trace the mental transformation of the narrator-protagonist throughout the text. The central ontological theme of the story is identified in the contrast between a mechanical, insect-like existence and an artistic, intellectually inclined mentality. Images and motifs deepening and complicating this dichotomy are explicated. These include the significance of different sensual impressions (hearing/noises vs. sight/vision) and various implications of the term order. In the conclusion, possible critical-theoretical contexts for interpretation are outlined: a potential feminist and a potential posthumanist reading are contrasted to an interpretation grounded in the author’s own view of literature as “ontologically transformed” language.